Constantine the African and ʻAlī ibn al-ʻAbbās al-Magūsī : the Pantegni and related texts - Burnett, Charles; Jacquart, Danielle. (Studies in Ancient Medicine, 1994)
When the tenth-century Kāmil as-sinā'a (or al-Kitāb al-malakī ) of 'Alī ibn al-'Abbās al-Mağūsī was adapted for a Latin-reading audience by Constantine the African in the late eleventh century, the medieval West had, for the first time, the opportunity to use a text which covered the whole of medicine. But the 100-odd extant manuscripts suggest that Contantine's Pantegni was put together over a considerable period of time, and chapters from other Latin and newly-translated Arabic medical works were added to or substituted those of the Kāmil . This book is the first to be devoted to Constantine the African: it sheds light on the School of Salerno and the formation of a medical corpus in the High Middle Ages.